The restorative effect of apocynin and catalase in l-arginine induced hypotension on normotensive subjects - the role of oxidative stress - Chia, T Y; Murugaiyah, V; Sattar, M A; Khan, N A K; Ahmad, A; Abdulla, M H; Johns, E J; Mei, H Y; Akhtar, S; Ahmad, F U (Physiological research, 2020)
L-arginine is a substrate for nitric oxide synthase (NOS) responsible for the production of NO. This investigation studied the effect of apocynin, an NADPH oxidase inhibitor and catalase, an H2O2 scavenger on L-arginine induced oxidative stress and hypotension. Forty Wistar-Kyoto rats were treated for 14 days with vehicle, L-arginine (12.5mg/ml p.o.), L-arginine+apocynin (2.5mmol/L p.o.), L-arginine+catalase (10000U/kg/day i.p.) and L-arginine plus apocynin+catalase respectively. Weekly renal functional and hemodynamic parameters were measured and kidneys harvested at the end of the study for histopathological and renal NADPH oxidase 4 (Nox4) assessments. L-arginine administration in normotensive rats decreased systolic blood pressure (120±2 vs 91±2mmHg) and heart rate (298±21 vs 254±15b/min), enhanced urinary output (21.5±4.2 vs 32±1.9ml/24h , increased creatinine clearance (1.72±0.56 vs 2.62±0.40ml/min/kg), and fractional sodium excretion (0.88±0.16 vs 1.18±0.16 %), caused proteinuria (28.10±1.93 vs 35.26±1.69mg/kg/day) and a significant decrease in renal cortical blood perfusion (292±3 vs 258±5bpu) and pulse wave velocity (3.72±0.20 vs 2.84±0.13m/s) (all P<0.05). L-arginine increased plasma malondialdehyde (by ~206 % P<0.05) and NO (by~51 %, P<0.05) but decreased superoxide dismutase (by~31 %, P<0.05) and total antioxidant capacity (by~35 %, P<0.05) compared to control. Renal Nox4 mRNA activity was approximately 2.1 fold higher (P<0.05) in the L-arginine treated rats but was normalized by apocynin and apocynin plus catalase treatment. Administration of apocynin and catalase, but not catalase alone to rats fed L-arginine, restored the deranged renal function and structure, prevented hypotension and enhanced the antioxidant capacity and suppressed Nox4 expression. These findings suggest that apocynin and catalase might be used prophylactically in states of oxidative stress.
Keywords: Oxidative Stress; oxidační stres; Catalase; Acetophenones; ledviny; Rats, Inbred WKY; NADPH-oxidasa 4; Kidney; krysa rodu Rattus; acetofenony; Antioxidants; zvířata; Arginine; potkani inbrední WKY; NADPH Oxidase 4; antioxidancia; katalasa; Pulse Wave Analysis; analýza pulzové vlny; krevní tlak; Male; arginin; hypotenze; Rats; Animals; Hypotension; mužské pohlaví; Blood Pressure; Disease Models, Animal; modely nemocí na zvířatech